1991
DOI: 10.1080/03610739108253889
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age on auditory event-related potentials

Abstract: The effects of age on event-related potentials (ERPs) elicited during a two-tone discrimination ("oddball") task were examined in 97 normal subjects aged from 17-80 years. Strong relationships were found between age and the latencies of the later ERP components N200 and P300. Furthermore the correlation between age and N200 latency at Pz was marginally higher than that of age and P300 latency. For the entire sample, the increase in P300 latency as a function of age was best described at Cz and Pz by linear reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 28 publications
2
15
0
1
Order By: Relevance
“…In studies on aging effects of ERP [Coyle et al, 1991;Fuchigami et al, 1993], latency shifts were found with a typical shortening towards adulthood, whereas amplitude shifts were less important. Thus, latencies were not evaluated in this study to avoid bias from aging.…”
Section: Passive Erpmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies on aging effects of ERP [Coyle et al, 1991;Fuchigami et al, 1993], latency shifts were found with a typical shortening towards adulthood, whereas amplitude shifts were less important. Thus, latencies were not evaluated in this study to avoid bias from aging.…”
Section: Passive Erpmentioning
confidence: 99%
“…It is known that aging effects predominantly involve peak latencies [Coyle et al, 1991;Fuchigami et al, 1993]. For this reason, latencies were not evaluated in this study; amplitudes were used instead.…”
Section: Multivariate Statistical Versus Neural Network Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…This was found for auditory as well as visual P300 paradigms. Interestingly, these age-related N200 latency prolongations ranging between 0.65 ms/year [83] and 0.90 ms/year [95] were smaller than those found for the P300 latencies but greater than that reported for the early 'exogenous' compo nents such as the N 1 and P2 [52], This finding is in good agreement with the general rule that the shorter the latency range of the compo nents, the smaller is the age-related latency prolongation, and vice versa. Furthermore, it also supports the above-mentioned assumpTable2.…”
Section: Aging and The N200 Componentmentioning
confidence: 99%
“…The relationship between P300 pa rameters and age may be described by differ ent mathematical models. While some au thors consider one linear regression function to be most suitable for both the P300 ampli tude and P300 latency from early adulthood to old age [52] [95] also found that the comparative analysis of linear regres sion functions in different age groups is most efficient and exponential regression models do not yield additional information.…”
mentioning
confidence: 99%